2021
DOI: 10.6061/clinics/2021/e2812
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer stents affect the final diameter of aortic aneurysms and maintain renal artery patency for a short time in a swine experimental model

Abstract: We sought to analyze the hemodynamic effects of the multilayer flow-modulated stent (MFMS) in Thoracoabdominal aortic aneurysms (TAAAs). METHODS: The hemodynamic effects of MFMS were analyzed in aortic thoracoabdominal aneurysms in experimental swine models. We randomly assigned 18 pigs to the stent or control groups and underwent the creation of an artificial bovine pericardium transrenal aneurysm. In the stent group, an MFMS (Cardiatis, Isnes, Belgium) was immediately implanted. After 4 weeks, we evaluated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…Of the 46 selected studies, 30, 15, and 1 reported swine, ovine, and bovine data, respectively. 2 , 10 53 In the 1 paper we found describing bovine arterial dimensions, only thoracic aorta measurements were determined to be relevant in this study. We found no study describing aortic arch branch diameters in calves and only 1 study in sheep reporting brachiocephalic trunk diameters.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 46 selected studies, 30, 15, and 1 reported swine, ovine, and bovine data, respectively. 2 , 10 53 In the 1 paper we found describing bovine arterial dimensions, only thoracic aorta measurements were determined to be relevant in this study. We found no study describing aortic arch branch diameters in calves and only 1 study in sheep reporting brachiocephalic trunk diameters.…”
Section: Resultsmentioning
confidence: 99%